Feasibility of utilizing autism navigator® for primary care in South Africa. Issue 11 (22nd October 2018) - Chambers, Nola J.; de Vries, Petrus J.; Delehanty, Abigail D.; Wetherby, Amy M.
Abstract : There is a significant research‐to‐practice gap in early detection of young children with autism spectrum disorder (ASD) worldwide but particularly in low‐ and middle‐income countries (LMICs) where expertise is limited and high‐quality training is difficult to access. Autism Navigator® for Primary Care is a web‐based course designed to increase awareness of red flags of ASD in the second year of life and thus promote earlier detection and referral for intervention. It contains extensive video illustrations that offer rapid access to multiple exemplars of ASD red flags. This study examined aspects of feasibility of the Autism Navigator® for Primary Care in one LMIC, South Africa. A mixed‐methods quasi‐experimental design was used to examine relevant professionals' implementation of the course and measure changes in their knowledge of red flags after training. Perceptions of the acceptability, demand, and practicality of the course were explored in focus groups. Sixty‐two providers completed the course online with a 94% completion rate. Built‐in learner assessment pass rates ranged from 88% to 100%. Second‐language English speakers took longer to complete the learner assessments, and professionals with less access to the Internet spent less time in the course. Participants' perceptions of the acceptability, demand, and practicality of the course were mostly positive with some suggestions made for local conditions. Results supported the feasibility of the course in this LMIC with some supports required pertaining to language and Internet access. We propose that this training has the potential to lower the age of detection of ASD in South Africa and other LMICs. Autism Research 2018, 11: 1511–1521 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Professionals in low‐ and middle‐income countries urgently need training to recognize red flags of autism in very young children. The feasibility of utilizing the Autism Navigator® for Primary Care course for this training was explored with 62 South African professionals. After training, professionals' knowledge of early red flags improved, and most reported the course important and needed in South Africa. They found the web‐based design mostly acceptable, practical, and culturally applicable. The course could help lower the age of autism detection.